Peninggalan Sejarah di Kabupaten Musi Rawas Sebagai Sumber Belajar Sejarah - Wicahyah, Diah; Susanti, L.R. Retno (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The Musi Rawas Regency is home to significant historical remnants, including the Ulak Lebar Site, an artifact from the pre historic era, along with the Bingin Jungut Site and the Tingkip Site, which are remnants of the Hindu-Buddhist period. These cultural treasures represent a valuable legacy from our ancestors, offering clear evidence of human civilization during both the pre historic and Hindu-Buddhist eras. This study aims to address the lack of local historical knowledge by introducing the history of Musi Rawas Regency through the effective management of cultural heritage sites, utilizing them as valuable sources for historical learning. The absence of a comprehensive understanding of history has resulted in these cultural heritage sites appearing foreign to the public and students alike. Therefore, leveraging cultural heritage sites as educational tools becomes crucial in addressing this knowledge gap. The research employs the historical method, focusing on locations such as Lubuklinggau, Bingin Jungut Village, Sungai Kijang Village, and SMA Negeri 2 Lubuklinggau. Education emerges as a proactive measure for preserving historical heritage in Musi Rawas Regency, emphasizing the utilization of cultural heritage sites as well-managed learning resources. This approach seeks to generate creative and innovative educational materials, aligning with the primary goal of capturing students' interest in history. Simultaneously, it aims to instill awareness of and appreciation for local history, fostering a deeper understanding of cultural heritage in Musi Rawas Regency. This initiative aspires to cultivate a community that values and preserves local history, ensuring the survival and maintenance of the original value of historical sites. By doing so, it anticipates the development of individuals who are not only knowledgeable about the region's history but are also actively engaged in safeguarding cultural heritage for future generations.